2008
DOI: 10.1099/vir.0.83396-0
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of surgical instruments from prions. II. In vivo findings with a model system for testing the removal of scrapie infectivity from steel surfaces

Abstract: The unusual resistance of agents causing transmissible spongiform encephalopathies (TSEs) to chemical or thermal inactivation requires special decontamination procedures in order to prevent accidental transmission of these pathogens by surgical instruments. In the search for effective, instrument-compatible and routinely applicable decontamination procedures, a previous study [Lemmer, K., Mielke, M., . J Gen Virol 85, 3805-3816] identified promising reagents in an in vitro carrier assay using steel wires conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 25 publications
6
48
0
2
Order By: Relevance
“…Moreover, high alkaline water (pH11.9 or more) can inactivate transmissible spongiform encephalopathies, the pathogens responsible for prion diseases. Since prion infection is a potential risk when using tissue engineered organs, 20 to ensure safety from prion disease, NaOH based decellularization solution has a significant advantage in regard to prion inactivation of the biomaterials. 21 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high alkaline water (pH11.9 or more) can inactivate transmissible spongiform encephalopathies, the pathogens responsible for prion diseases. Since prion infection is a potential risk when using tissue engineered organs, 20 to ensure safety from prion disease, NaOH based decellularization solution has a significant advantage in regard to prion inactivation of the biomaterials. 21 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…Paraffin-embedded Tissue (PET) Blotting-PET blotting was performed as described previously (25) with midsagittal brain sections.…”
Section: Animals Tse Agents and Prpmentioning
confidence: 99%
“…A titre analysis of these results performed in analogy to the method of Spearman-Kärber revealed that 1.0 Â 10 27.0 g (standard deviation: 0.6 logarithmic 10 units) of the 263K stock (from previous titrations in hamster bioassays known to carry about 1 Â 10 2 intracerebral ID 50 ) contained one CCID 50 in the cell assay performed with a cultivation period of 40 DPE. 25,28 . ...........................................................................................................................................…”
Section: Resultsmentioning
confidence: 99%